Linking Ocean Forcing and Atmospheric Interactions to Atlantic Multidecadal Variability in MPI-ESM1.2 - Oelsmann, J.; Borchert, L.; Hand, R.; Baehr, J.; Jungclaus, J. H. (Geophysical Research Letters, 2020)
We investigate how ocean-driven multidecadal sea surface temperature (SST) variations force the atmosphere to jointly set the pace of Atlantic multidecadal variability (AMV). We generate periodic low-frequency Atlantic Meridional Overturning Circulation oscillations by implementing time-dependent deep-ocean-density restoring in MPI-ESM1.2 to explicitly identify variations driven by Atlantic Meridional Overturning Circulation without any perturbation at the ocean-atmosphere interface. We show in a coupled experiment that ocean heat convergence variations generate positive SST anomalies, turbulent heat release, and low sea level pressure in the subpolar North Atlantic (NA) and vice versa. The SST signal is communicated to the tropical NA by wind-evaporative-SST feedbacks and to the North-East Atlantic by enhanced northward atmospheric heat transport. Such atmospheric feedbacks and the characteristic AMV-SST pattern are synchronized to the multidecadal time scale of ocean circulation changes by air-sea heat exchange. This coupled ocean-atmosphere mechanism is consistent with observed features of AMV and thus supports a key role of ocean dynamics in driving the AMV.